Labor force participation during COVID-19 economic crisis in Mexico: care work demands and differential recovery between men and women - Carnes Borrajo, Lía (2022)
The COVID-19 pandemic not only has had an impact in public health field, but it has also lead to a profound social and economic crisis. Attending to the demands generated by the virus has meant an economic standstill almost everywhere in the world. Mexico wasn’t the exception and the measures implemented in the country had important consequences in the economy and the labor market, carrying to a strong reduction of employment and withdrawals from the labor force. Thus, this article looks to understand the observed differences in this process, taking a point of view which prioritizes household care demands as a factor that can explain the dissimilar behaviour by gender.  To follow this objective a quantitative analysis is performed using data from the ECOVID-ML, through a logistic regression model. This shows that the effect of the care variables is relevant in understanding differences in labor force participation between men and women, and also confirms the lower reincorporation into the labor market of women, even though recovery has concentrated on feminized sectors.